Construction of extended technology acceptance model of electronic medical records in Jordan: The influence of doctors’ self-efficacy and perceived behavioral control - Khorma, Ola Thaseer; Baharom, Fauziah; Mohd, Haslina (2010)
The implementation of Electronic Medical Record (EMR) in Jordan public hospitals has started since 2009.The motivation of doing this study is to observe doctors’ acceptance of EMR in Jordanian public hospitals.This study aims at constructing doctors’ acceptance model of EMR using Technology Acceptance Model (TAM) based on individual capabilities.The model will apply TAM as the basic theory and extending Self-Efficacy (SE) and Perceived Behavioral Control (PBC) as two factors of individual characteristics. Initial findings show that the main factors of the model should compose of Perceived Usefulness, Perceived Ease of Use, Behavioral Intention to Use, Self-Efficacy, and Perceived Behavioral Control.The result of the pilot test shows that all factors are reliable with Cronbach Alpa 0.838.The recommendation to the top management of healthcare organization, in order to increase doctors’ acceptance of EMR, that the new deployment of EMR should focus on delivering awareness and continuous training on using EMR among doctors at the early stage of EMR implementation .